2020
DOI: 10.1016/j.ejphar.2020.173089
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric arterial dysfunction in the UC Davis Type 2 Diabetes Mellitus rat model is dependent on pre-diabetic versus diabetic status and is sexually dimorphic

Abstract: Previous reports suggest that diabetes may differentially affect the vascular beds of females and males. However, there is insufficient evidence to establish the timeline of the vascular dysfunction in diabetes, specifically in relation to sex. Here, we determined whether mesenteric arterial function is altered in UC Davis Type-2 Diabetes Mellitus (UCD-T2DM) rats and if this occurs as early as the pre-diabetic stage of the disease. Specifically, we investigated whether vascular dysfunction differs between pre-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 66 publications
(78 reference statements)
3
22
0
Order By: Relevance
“…In the current study, while both male and female diabetic rats had higher body weight and hyperglycemia compared with non-diabetic control rats, the female diabetic group exhibited higher adiposity, triglyceride, and insulin levels than control or male diabetic rats. This is consistent with the results from our previous study (Shaligram et al, 2020). Similarly, Ohta et al (2014) which reported elevated blood insulin levels in spontaneously diabetic torii (SDT) female rats compared with SDT male rats.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the current study, while both male and female diabetic rats had higher body weight and hyperglycemia compared with non-diabetic control rats, the female diabetic group exhibited higher adiposity, triglyceride, and insulin levels than control or male diabetic rats. This is consistent with the results from our previous study (Shaligram et al, 2020). Similarly, Ohta et al (2014) which reported elevated blood insulin levels in spontaneously diabetic torii (SDT) female rats compared with SDT male rats.…”
Section: Discussionsupporting
confidence: 93%
“…Fasting plasma insulin concentration was significantly higher in female diabetic rats compared with those in both the non-diabetic female control and male diabetic groups (Table 1). Similar to the previous report (Shaligram et al, 2020), there was no difference in plasma insulin levels in male diabetic rats when compared with their respective non-diabetic controls. However, the ISI was significantly lower in diabetic groups, regardless of sex, indicating that insulin signaling may be impaired in diabetic groups of both sexes.…”
Section: Metabolic Parameters and Insulin Signaling In Ucd-t2dm Ratssupporting
confidence: 90%
See 1 more Smart Citation
“…Elevated fasted plasma glucose >200 mg/dl lagged the detection of the elevated fed blood glucose levels by 2 months (Cummings et al., 2008). Levels of HbA1c >6% in combination with blood glucose concentrations have also been used as criteria to define diabetic groups for both male and females (Akther et al., 2021; Shaligram et al., 2020). Fasting HbA1c increased 2.25‐fold (from 4 to 9%) in UCD‐T2M rats fed regular diet from 2 to 6 months of age (Cummings, Stanhope, Graham, Baskin et al., 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Studies conducted ex vivo with isolated blood vessels indicate that endothelial function with respect to vasodilator mechanisms is altered in the prediabetic and diabetic UCD‐T2DM rats (Akther et al., 2021; Shaligram et al., 2020). In female and male UCD‐T2DM rats, mesenteric arterial vasodilatation in response to the muscarinic agonist acetylcholine was reduced by 20 and 70%, respectively, in diabetic (6.7 to 8.5 weeks) compared with prediabetic groups (Shaligram et al., 2020). Mesenteric arterial vasodilatation was 24% less in male, but not in female, prediabetic UCD‐T2DM rats compared with age‐ and sex‐matched SD rats (Shaligram et al., 2020).…”
Section: Resultsmentioning
confidence: 99%